Potential role of 25(OH)D insufficiency in the dysfunction of glycolipid metabolism and cognitive impairment in patients with T2DM - Sun, Hui-min; Yu, Yue; Gao, Xin-ran; Wei, Ya-dong; Qi, Chuan-zong; Ma, Meng-die; Xu, Dan-dan; Xu, Ya-yun; Ge, Jin-fang (Frontiers in Endocrinology, 2022)
Purpose: To investigate the changes of plasma 25(OH)D levels in type 2 diabetes mellitus (T2DM) patients and explore its role in the dysfunction of glucose and lipid metabolism and cognition. Methods: One hundred and thirty-two T2DM patients were enrolled and the demographic and clinical data were collected. The plasma concentration of 25(OH)D was detected and the patients were divided into two groups including a Vitamin D insufficient (VDI) group and a normal VD group according to the clinical diagnostic criterial of VDI with the plasma 25(OH)D level less than 29 ng/mL. The glycolipid metabolic and routine blood biochemical indices were detected, the plasma concentrations of C-reactive protein (CRP), interleukin-6 (IL-6), soluble myeloid soluble trigger receptor 1 (sTREM1) were measured. The cognitive function was assessed using the Behavior Rating Inventory of Executive Function-Adult Version (BRIEF-A). The depressive symptomatology was assessed using the Center for Epidemiological Survey Depression Scale (CES-D). Sleep quality was assessed using the Pittsburgh sleep quality index (PSQI). Results: There were 70 T2DM patients with VDI (70/132, 53.03%) in this study. The plasma concentrations of glycated hemoglobin (HbA1c), fasting plasma glucose (FPG), postprandial blood glucose (PBG), IL-6, and sTREM1 were remarkably increased in T2DM patients with VDI as compared with that with the normal VD, accompanied with an elevated BRIEF-A scores. There was no significant difference between groups with regard to the indices of blood lipid, liver function, and scores in CES-D and PSQI. Moreover, results of Pearson correlation test showed that the plasma 25(OH)D levels were negatively correlated with HbA1c, FPG, PBG, CRP, IL-6, sTREM1, CES-D sum scores, and PSQI sum scores, but positively correlated with the plasma levels of Serum creatinine (Scr). Furthermore, result of Receiver Operating Characteristic (ROC) curve analysis showed a predictive role of VDI levels in discriminating T2DM patients with higher cognitive impairments, with the sensitivity and specificity being 62.12% and 62.12%, respectively. Conclusion: VDI is harmful for T2DM patients with a significant relation with the hyperglycosemia and cognitive dysfunction.